Being human during COVID - Hass, Kristin Ann, 1965- (Michigan humanities collaboratory, 2021)
Science has taken center stage during the COVID-19 crisis; scientists named and diagnosed the virus, traced its spread, and worked together to create a vaccine in record time. But while science made the headlines, the arts and humanities were critical in people's daily lives. As the world went into lockdown, literature, music, and media became crucial means of connection, and historians reminded us of the resonance of the past as many of us heard for the first time about the 1918 influenza pandemic. As the twindemics of COVID-19 and racial injustice, embodied in mass protests following the death of George Floyd and other police-committed violence, tore through the United States, a contested presidential race unfolded, which one candidate described as "a battle for the soul of the nation." Being Human During COVID' documents the first year of the pandemic in real time, bringing together humanities scholars from the University of Michigan to address what it feels like to be human during the COVID-19 crisis. Over the course of the pandemic, the questions that occupy the humanities-about grieving and publics, the social contract and individual rights, racial formation and xenophobia, ideas of home and conceptions of gender, narrative and representations and power-have become shared life-or-death questions about how human societies work and how culture determines our collective fate. The contributors in this collection draw on scholarly expertise and lived experience to try to make sense of the unfamiliar present in works that range from traditional scholarly essays, to personal essays, to visual art projects. The resulting book is shot-through with fear and dread and frustration and prejudice, and, on a few occasions, with a thrilling sense of hope.